'The island is full. Please don't come': Narratives of austerity and migration in a UK citizenship class. Issue 5 (3rd October 2017) - Tuckett, Anna
Abstract : In the lead up to, and aftermath of, the UK referendum on its membership of the European Union, issues relating to migration and entitlement dominated public debates. In a ruthless campaign, the 'Leave' camp exploited the implementation of years of austerity policies by explicitly correlating their negative effects with supposedly high migrant numbers. Examining the discourses of scarcity, austerity and deservingness which prevailed during the referendum campaign, this article discusses the way in which UK citizenship classes act as spaces for both the reproduction and subversion of these narratives. On the one hand, migrants in the classes reproduce discourses which scapegoat other migrants for the effects of austerity. On the other, however, powerful messages about the fundamental human right to migrate are also championed.